179 Assessment of Erectile and Ejaculatory Functions after Bladder-Sparing Therapy Against Muscle-Invasive Bladder Cancer. (1st May 2022) - Uchida, Y.; Yokoyama, M.; Nakamura, Y.; Fukuda, S.; Uehara, S.; Tanaka, H.; Yoshida, S.; Matsuoka, Y.; Fujii, Y.
ABSTRACT: Introduction: Radical cystectomy (RC) is still gold standard for muscle invasive bladder cancer (MIBC). Whereas, bladder-sparing therapy with transurethral resection of bladder tumor (TUR) and chemoradiation therapy (CRT) has been recognized as an alternative treatment to RC for selected patients with MIBC. We have developed and implemented tetra-modality bladder-sparing therapy (TeMT) incorporating partial cystectomy (PC) in addition to maximal TUR and induction CRT to overcome local recurrence after bladder-sparing therapy (Kageyama et al. Am J Clin Oncol 2003, Koga et al. BJU Int 2012, Kijima et al. BJU Int 2019). There are few studies on erectile and ejaculatory functions after bladder-sparing therapy. Objective: To cross-sectionally survey erectile and ejaculatory functions after TeMT in patients with MIBC. Methods: Of the total 117 male patients with MIBC who completed TeMT between 2006 and 2019, 70 patients were set as the target to distribute the questionnaires after excluding patients lost to follow up as of February 2020, patients with local recurrence of MIBC or additional prostate cancer treatment. Erectile function was assessed using the International Index of Erectile Function short form (IIEF-5), and ejaculatory function using Male Sexual Health Questionnaire Ejaculatory Dysfunction short form (MSHQ-EjD-SF). Attending physicians handed the questionnaires to the patients at the first regular outpatient visit after February 2020 and had the patients complete them outside the office. Results: Of 44 patients received the questionnaires between February and August 2020, 35 completed the questionnaires. The median age (range) of the eligible patients was 70 (50-87) years old, and the median time from the date of PC to the date of response was 5.2 (0.35-14) years. The results of IIEF-5 showed that 3 (9%) had no erectile dysfunction (ED) (22-25 points), 9 (26%) had mild ED (17-21 points), 4 (11%) had mild to moderate ED (12-16 points), 4 (11%) had moderate ED (8-11 points), and 15 (43%) had severe ED (5-7 points). Based on the results of MSHQ-EjD-SF, 23 patients (66%) responded that they could ejaculate. Of those, 5 patients (14%) scored 4 or higher on all questions 1-3 of MSHQ-EjD-SF, suggesting that they did not have ejaculatory dysfunction. Conclusions: Preservation of erectile and ejaculatory functions was observed in MIBC patients treated with bladder-sparing therapy. Along with that of lower urinary tract function, preservation of male sexual function in bladder-sparing therapy, especially ejaculatory function which is inevitably lost by RC, is considered to be an advantage over RC. Disclosure: Work supported by industry: no.